Nursing of a patient with respiratory failure using electrical impedance tomography for monitoring local pulmonary ventilation (1例肺电阻抗成像指导下呼吸衰竭患者的护理) - DU Lingshuang (杜灵爽); WANG Ran (王然) (中西医结合护理)
This paper summarized the nursing cooperation of electrical impedance tomography(EIT) for monitoring local pulmonary ventilation in a patient with respiratory failure and decreased oxygenation. By using the EIT for monitoring local pulmonary ventilation, targeted interventions such as postural drainage and vibration sputum expectoration were carried out, and the changes of oxygenation were recorded. The EIT-guided chest physiotherapy is effective to improve the pulmonary ventilation and oxygenation of the patient with respiratory failure (总结1例呼吸衰竭患者氧合指数反复降低应用肺部电阻抗成像技术(EIT)监测指导操作的护理过程。利用EIT技术监测患者肺通气情况, 并针对性的给予体位引流及振动排痰, 记录操作前后氧合指数变化。患者肺部通气情况好转, 氧合指数明显改善, 转出ICU后专科治疗。EIT 技术指导下行胸部物理治疗, 有助于患者肺通气状况及氧合指数的改善。)